Hyperthermic intraperitoneal chemotherapy for the treatment of recurrent ovarian cancer in elderly women. (11th February 2015) - Delotte, Jérôme; Arias, Tatiana; Guerin, Olivier; Boulahssass, Rabia; Bereder, Isabelle; Bongain, André; Benchimol, Daniel; Bereder, Jean Marc
Abstract Our aim was to evaluate the morbidity and survival associated with combined cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) in the treatment of recurrent ovarian cancer for patients aged 70 years and older. We conducted a monocentric study in a French university hospital and collected data on 15 women aged ≥70 years, treated by cytoreduction and HIPEC for ovarian cancer relapse. The median overall survival was 35 months, with a median disease‐free survival of 15.6 months. When a Peritoneal Cancer Index subgroup analysis was performed, a statistically significant difference in the disease‐free survival could be observed for a Peritoneal Cancer Index ≤13 (p = 0.036). A trend towards improvement of disease‐free survival was observed when the Completeness of Cytoreductive Score was equal to 0 (p = 0.0915).